(untitled) (Annals of Medical Research, 2021)
Aim: Corticosteroids are widely used to prevent and treat bronchopulmonary dysplasia (BPD) due to their strong anti-inflammatory effects. We aim to evaluate the outcomes of late onset systemic hydrocortisone (HC) therapy in very low birth weight infants with BPD.Material and Methods: The medical records of 706 preterm infants with gestational age ≤ 30 weeks over a 4-year period were retrospectively reviewed. Infants who required invasive/noninvasive respiratory support or ≥ 30% oxygen due to BPD and were treated with HC after the third postnatal week were included. The infants were divided into 3 groups according to respiratory support at the beginning of the HC treatment: mechanical ventilation (MV), noninvasive ventilation (NIV), and free oxygen.Results: Seventy-six (11.9%) infants in our cohort received HC therapy. In the MV group, 83.3% of the infants were successfully extubated after a median of 4 days (interquartile range [IQR], 2-8 days). In the NIV group, 83.9% of the infants required no longer respiratory support after a median of 6 days (IQR, 3-16 days). In the free oxygen group, none of the infants needed supplemental oxygen after a median of 8 days (IQR, 6-12 days). Conclusion: Late HC therapy facilitates extubating without adverse short-term effects, reduces the need of invasive and noninvasive ventilation, and facilitates discharge without supplemental oxygen.